Composition, tensile strength, and elastic modulus of Orden as cast post alloy - Anggraini, Novi; Hasratiningsih, Zulia; Subrata, Gantini (Padjadjaran Journal of Dentistry, 2010)
Post is one element of the fixed restorations that is generally used to restore endodontically treated teeth at Prosthodontic Installation of Oral and Dental Hospital (RSGM) Faculty of Dentistry Universitas Padjadjaran, whereas Orden alloy is still used as cast post material. The faculty supplies Orden without packaging or manuals, so the information about its composition and mechanical properties are not available. This study was conducted to search the composition, tensile strength, and elastic modulus of Orden. For the composition test, a specimen with size 20x20x2 mm3 was tested with Optical Emission Spectroscopy (OES). For tensile test, 6 specimens were made according to ASTM Standard E8. While for bending test, 6 specimens were made according to ASTM Standard E855. The Universal Testing Machine Instron 1195 was used to test the tensile strength and elastic modulus. The value of tensile strength of Orden was compared to gold alloy type III and the value of elastic modulus of Orden was compared to dentin. Composition test found that Orden was a brass with the largest ingredient of copper 53.76 wt%, followed by zinc 44.94 wt%, and aluminum 1.17 wt%. The statistic calculation showed that tensile strength of Orden was lower than gold alloy type III and the elastic modulus of Orden was higher than dentin.